2020
DOI: 10.2139/ssrn.3682745
|View full text |Cite
|
Sign up to set email alerts
|

Declining Industrial Disruption

Abstract: Recent research finds that markups are rising, suggesting declining competition. But does less price competition mean less Schumpeterian "creative destruction"/industry dynamism? This paper reports the first recent estimates of trends in the displacement of industry-leading firms. Displacement hazards rose for several decades since 1970 but have declined sharply since 2000. Using a production function-based model to explore the role of investments, acquisitions, and lobbying, we find that investments by domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…Specifically, a 10percentage-point increase in industry concentration corresponds to a 0.6-percentage-point reduction in the share of new firms among the top 8 (a 4% reduction compared to the mean share), a 1-percentage-point increase in the year-on-year rank correlation of firm's market shares within the top 8 (a 1.1% increase compared to the mean value) and a 0.14-percentage point reduction in the market share instability (a 9% reduction compared to the mean value). These results are in line with evidence found for the US (Bessen et al, 2020) showing that the displacement of industry-leading firms has declined sharply since 2000 and that the greater persistence at the top is closely linked to investments in proprietary software by dominant firms.…”
Section: Industry Concentration and Measures Of Business Dynamics And Competitionsupporting
confidence: 90%
“…Specifically, a 10percentage-point increase in industry concentration corresponds to a 0.6-percentage-point reduction in the share of new firms among the top 8 (a 4% reduction compared to the mean share), a 1-percentage-point increase in the year-on-year rank correlation of firm's market shares within the top 8 (a 1.1% increase compared to the mean value) and a 0.14-percentage point reduction in the market share instability (a 9% reduction compared to the mean value). These results are in line with evidence found for the US (Bessen et al, 2020) showing that the displacement of industry-leading firms has declined sharply since 2000 and that the greater persistence at the top is closely linked to investments in proprietary software by dominant firms.…”
Section: Industry Concentration and Measures Of Business Dynamics And Competitionsupporting
confidence: 90%
“…The results in this paper contribute a detailed story of endogenous polarization as one potential driver of increasing industry concentration to the (mostly) empirical discussion. Within the model, I show that a phase of acceleration in technological progress implies higher market concentration (Bessen, 2020) accompanied by stronger divergence between leaders and laggards in productivity (Andrews et al, 2015) and skills (Song et al, 2019) and a reduction in industrial dynamics (Bessen et al, 2020). The dominant force behind these findings is a virtuous / vicious cycle between firms' vintage choice and their wage offers on the labor market.…”
Section: Introductionmentioning
confidence: 89%
“…Only about half of the German population considers entrepreneurship to be a good career choice, which is lower than the OECD average and much lower than the 70% in the United States and the 80% in the Netherlands (Jones & Jin, 2017). From an innovation point of view, the stagnation in entrepreneurship is of concern as it means that it has not been as effective in producing and commercialising innovations in recent times as during earlier periods, and has become less 'Schumpeterian', i.e., less disruptive and less likely to displace existing firms (Bessen et al, 2020;Henrekson & Sanandaji, 2017). This is a reason for the dearth of radical innovations as well as for the slower diffusion of technology.…”
Section: Entrepreneurship Stagnationmentioning
confidence: 99%
“…These features result in reduced competition, which has both static and dynamic negative effects, the latter in particular resulting in reduced disruptive innovation. For the United States, Bessen et al (2020) found that reduced competition has indeed been accompanied by less risk of displacement of incumbent firms since 2000.…”
Section: Entrepreneurship Stagnationmentioning
confidence: 99%